Taxing highly processed foods: What could be the impacts on obesity and underweight in sub-Saharan Africa? - Boysen, Ole; Boysen-Urban, Kirsten; Bradford, Harvey; Balié, Jean (Elsevier, 2019)
The consumption of highly processed food has been singled out as one of the factors responsible for the rapidly increasing prevalence of obesity and its associated non-communicable diseases and costs. While obesity prevalence is still comparatively low in lower-income sub-Saharan Africa (SSA), development prospects in this region render markets especially attractive for these foods, whose consumption is already growing at higher rates than in developed countries. This might be reflected in the massive rise in obesity prevalence growth rates in SSA over the past decade, while many of these countries are simultaneously struggling with high undernutrition prevalence. Using a newly constructed cross-country panel dataset, this study econometrically investigates the effect of higher import tariffs on highly processed vis-à-vis less-processed foods with respect to their impacts on obesity and underweight prevalence in the adult population. While the analysis is global, the discussion focuses primarily on SSA. The effects of the tariff differences are found to be significant and substantial and to differ by income level of the country as well as by gender. More generally, the results show that policies affecting the consumer price differential between the two food groups are effective in influencing obesity and underweight prevalence and that these two issues cannot be treated separately.